(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
By its judgment n. 242/2019 the Italian Constitutional Court declared the legitimacy of the medically assisted suicide request, justifying it on the same constitutional parameters that guarantee the right to renounce life support treatments. This essay confirms, from a bioethical perspective, the need to keep the two choices separated, bringing out both the difficulties due to profiles of equality between patients in similar conditions and the lack of palliative care in some Italian regions. Overall, the evident concern is a judgment which, for the purpose of access to assisted suicide, generalizes conditions taken by the “exceptional” case of Fabiano Antoniani.